CERPEN BEGAL DAN OGOH-OGOH DALAM PUPULAN CERPEN BEGAL: ANALISIS PSIKOLOGI SASTRA - Ksatriani, Kade Gita (Humanis; Volume 5. No. 3. Desember 2013)
Analysis of the psychology literature of Begal and ogoh-ogoh aims to describe the structural aspects and psychological aspects of character. Theory used in this study are structural theory and the theory of personality psychology. Methods and techniques used in this study were divided into three stages. Methods and techniques used in this study were divided into three stages. Methods and techniques of providing data, methods and techniques of data analysis, data presentation methods and techniques. At the stage of providing data using method of listening that assisted with recording techniques and translation techniques. Stage of data analysis using qualitative and descriptive analytic techniques. Stage presentation of data using informal methods of deductive and inductive techniques. Results achieved in this study the structure of Begal and ogoh-ogoh that includes incident, character and characterization, setting, theme and mandate. Moreover, the psychological aspects of characters Begal and ogoh-ogoh that includes the id, ego, and superego
Keywords: short story, structure, psychology